(untitled) (Bangladesh Agronomy Journal, 2025)
The experiment was conducted at Agronomy research field of Bangladesh Agricultural Research Institute, Gazipur during 2018-2019 and 2019-20 to find out the optimum fertilizer dose and appropriate weed management method for getting higher yield and economic return of black cumin. The treatments were T1= STB (Soil test basis fertilizer dose, FRG, 2018) 60-24-49-13-0-1 kg ha−1 of N- P- K- S- Zn- B and two hand weeding at 30 days after emergence (DAE) and 50 DAE of black cumin, T2= STB + 25% of N-P-K kg ha−1 and two hand weeding at 30 DAE and 50 DAE of black cumin, T3= STB + 50% of N-P-K kg ha−1 and two hand weeding at 30 DAE and 50 DAE of black cumin, T4= STB and two hand spading at 30 DAE and 50 DAE of black cumin, T5= STB + 25% of N-P-K kg ha−1 and two hand spading at 30 DAE and 50 DAE of black cumin ,T6= STB + 50% of N-P-K kg ha−1 and two hand spading at 30 DAE and 50 DAE of black cumin and T7 = Native nutrient and no weeding (Control). The highest weed control efficiency % (WCE) 83.68 and 85.23% at 30 DAE of black cumin and 93.62% and 92.57% at 50 DAE of black cumin was found in T3 treatment (Two hand weeding at 30 DAE of black cumin and 50 DAE of black cumin with STB + 50% of NPK kg ha−1 fertilizer dose) in 2018-2019 and 2019-2020, respectively followed by T2 (82,35 to 82.74% and 92.24 to 91.24%) treatment at 30 and 50 DAE of black cumin and in 2018-19 and 2019-20 respectively. Results showed that treatment T3 (STB + 50% of N-P-K kg ha−1 and two hand weeding at 30 and 50 DAE of black cumin) produced the highest seed yield 953.75 kg ha−1 but in case of higher benefit cost ratio 2.69 was obtained from T4 treatment (soil test basis fertilizer dose: 60-24-49-13-0-1 kg ha−1 of N-P-K-S-Zn-B kg ha−1 and two hand spading at 30 and 50 DAE of black cumin) due to lower cost of production. Bangladesh Agron. J. 2025, 28(1): 8-16